Assessment of Seed Infestation Level of Brown Spot (Bipolaris Oryzae) in Different Rice Genotypes under Natural Epiphytotic Conditions - Pantha, Prakash; Yadav, Dil Raj (International Journal of Applied Sciences and Biotechnology, 2016)
Bipolaris oryzae, the causal agent of brown spot disease, is an economically important pathogen of rice found in several rice growing countries in the world. Seed samples were collected from the rice experimental field comprised of different rice genotypes at National Rice Research Program, Hardinath, Dhanusha, Nepal in 2014 to determine the infestation level of B. oryzae and taxonomic identification of seed borne fungi by standard blotter method. The major recovered fungal mycoflora were B. oryzae, Pyricularia oryzae, Ustilaginoidea virens, Aspergillus flavus, Aspergillus niger, Curvularia oryzae, Rhizopus oryzae, Alternaria sp., Cercospora sp. and Penicillium sp. Seeds of all rice genotypes were infected with these fungi however frequency of fungal association varied among rice genotypes (from 12% to 96%). The percentage infection of B. oryzae was recorded maximum in all the rice genotypes compared to other seed-borne fungi. Madhaya dhan 845 and BI-0530-5-10-1-2 were the most infected genotypes and the infection percentage was 72% and 68%, respectively. Similarly, the least infected genotypes were Sabitri and TN-1 and infection level of 8% was recorded in both genotypes. Our findings may be used to predict disease occurrence and fungal transfer to new uninfected areas. Moreover, this study suggests that rice seed should be properly detected to check contamination by pathogens before sowing for effective and healthy crop production. Int J Appl Sci Biotechnol, Vol 4(3): 294-297